ОКРЕМІ НАПРЯМИ ПРОЕКТУВАННЯ ПОЛІЦЕЙСЬКОЇ ДІЯЛЬНОСТІ ЯК ЗАСОБУ ЗАПОБІГАННЯ ВУЛИЧНІЙ ЗЛОЧИННОСТІ - Бєліков, Костянтин Аркадійович (SUPREMANCE OF LAW, 2019)
The article presents the current directions of designing police activities as a means of preventing street crime. It is argued that the state and dynamics of street crime and the functioning of the system to prevent it, without exaggeration, is an indicator of the socio-economic and cultural climate of any society. Given the specifics of crimes committed in street conditions, the lions share of counteraction to these socially dangerous acts and the development of measures to prevent are the responsibility of the bodies and units of the National Police of Ukraine. The specified state body has all the necessary powers to develop a wide variety of measures in the field of street crime prevention. The need for the functioning of such police units as the situational center and the only analytical service center has been updated. The feasibility of developing and implementing projects of police practices aimed at: preventing violence during mass events; promoting partnerships between the police and society; promoting police service and engaging civilian youth in police service; creating a safe environment in the community; the formation of a favorable socio-psychological climate in educational institutions, a decrease in the crime rate among minors. Th e possibilities of introducing comprehensive targeted programs aimed at preventing street crime were also analyzed. Structurally investigated are such programs as youth crime prevention (should be carried out at three levels) and programs for the prevention of illicit trafficking in narcotic drugs and psychotropic substances. It was stated that the prevention of street crime requires the bodies and units of the National Police, as well as local communities, to consolidate efforts with a view to joint interaction. The most effective way of such interaction is to introduce programs and projects to the most common crimes committed in the street.